RSIS Series on Malaysia's 14th General Election - GE14 & the Future of Malay Politics - Yang Razali Kassim (2018)
This general election is poised to be game-changing, at the core of which will be the future of Malay politics. Will it resist the undercurrents of change? Or will Malay politics in Malaysia take a new turn, bringing along with it an altered political landscape?